Microwave-Assisted Acid Hydrolysis vs. Conventional Hydrolysis to Produce Sapogenin-Rich Products from Fenugreek Extracts - Joaquin Navarro del Hierro; Emma Cantero-Bahillo; M. Teresa Fernández-Felipe; Diana Martin (Foods, 2022)
The acid hydrolysis of saponins is commonly performed by conventional heating to produce sapogenin-rich products of bioactive interest, but alternative hydrolysis methods and their impact on bioactivity have been unexplored. We compared the conventional method with microwave-assisted acid hydrolysis (MAAH) of a commercial saponin-rich extract from a typical saponin source, fenugreek, focusing on the study of temperature (100, 120, 130, 140, 150 °C) and time (10, 20, 30, 40 min) of hydrolysis. The impact of these factors was assayed on both the sapogenin yield and the bioactivity of the hydrolyzed products, specifically their antioxidant and lipase inhibitory activities. The highest sapogenin content (34 g/100 g extract) was achieved by MAAH at 140 °C and 30 min, which was higher than conventional hydrolysis at both reference conditions (100 °C, 60 min, 24.6 g/100 g extract) and comparative conditions (140 °C, 30 min, 17 g/100 g extract) (p < 0.001). Typical steroid artifacts from sapogenins were observed in very small amounts, regardless of the method of hydrolysis. Antioxidant activity of MAAH hydrolyzed extracts (around 80% DPPH inhibition) was barely affected by time and temperature, but pancreatic lipase inhibitory activity was higher (>65%) at lower MAAH temperature (<130 °C) and time (<30 min) of hydrolysis. MAAH is shown as a valid alternative to produce selective sapogenin-rich extracts from fenugreek with minor impact on their bioactivities, and whose magnitude can be modulated by the hydrolysis conditions.